POLITICAL INSTABILITY AND INFORMALITY IN UGANDA: AN EMPIRICAL ANALYSIS - Esaku, Stephen (The European Journal of Applied Economics, 2021)
In this paper, we analyze the long-run relationship between political instability and the shadow economy in Uganda using the autoregressive distributed lag bounds testing approach to cointegration. We find a negative and statistically significant relationship between political instability and the shadow economy, in both the long-run and short-run. This implies that an improvement in political processes that create stability in the incumbent regime significantly reduces the shadow economy, consistent with the view that political institutions play a crucial role in facilitating political processes, which in turn reinforce the allocation of economic resources and the provision of public goods and services that improve the welfare of the citizens. This makes it less attractive for the citizens to operate in the shadow economy as the formal economy can now provide much of the needed goods and services. The practical implication of these results is that any attempts by policy makers to reduce activities in the shadow economy should also involve reforming the political system and encouraging civic engagement between the political elites and the citizenry or voters. Additionally, policy makers should formulate policies that reinforce the functioning of political institutions independent of any interference from political elites with rent-seeking behavior.